Penggunaan Media Pembelajaran Berbasis E-Learning Terhadap Motivasi Belajar Biologi Siswa - Aroyandini, Elvara Norma; Anfa, Qurrotul; Firanti, Annisa (BIO-EDU: Jurnal Pendidikan Biologi, 2021)
One of the main problems in learning biology is the lack of student motivation in learning. This is partly due to the lack of learning media that can visualize learning more exciting and easily understood by students without multiple interpretations due to not seeing the real learning object. Therefore, this study was conducted to determine the types or variants of e-learning media in biology learning and analyze the background problems based on previous studies of previous studies. The method used in this research is a literature study with a pure research style. The data collection technique is a library research technique with data sources in reference books and 37 articles relevant to research topics in the period 2013 to 2020. Data analysis is carried out using content analysis and exploration models, where the analysis results are used as a basis for interpretation. Based on the discussion that has been done, it can be concluded that this study found 15 types of e-learning media in biology learning that can increase student learning motivation, where the most influential media are android applications, interactive multimedia, animation, and original el-learning. In addition, it was also found that the background that caused the students' low motivation to learn was due to the lack of technology development in biology learning media, the lack of visualization of various objects of biology learning, and the lack of student interest in participating in biology learning.